Available soil water upper limit by modeling and direct determination in a greenhouse - Campos, Matheus Pena; Rufini, José Carlos Moraes; Silva, Bruno Montoani; Sousa, Saulo Saturnino de; Magalhães, Deniete Soares; Campos, Pedro Henrique Pena (Scientia Agraria Paranaensis, 2019)
Pot capacity (PC) is a direct method of determining field capacity (FC) for experiments with plantings in pots. The objective of this study was to evaluate different laboratory methods to determine field capacity and compare them with the pot capacity method. The experimental design was completely randomized (CRD), with nine treatments (methods of obtaining FC) and four replications, totaling 36 experimental plots. The mean values of moisture contents in the FC of the nine methods were compared, being eight empirically obtained and one directly in the greenhouse, defined as a control treatment (PC). The relative accuracy (RA) for all treatments was determined in relation to the control treatment. The estimation of the upper limit of available water in the soil varies depending on the method, and a decreasing order of moisture levels can be observed at FC: FC-Lab4pts > FC-Labip > FC-Lab8pts > PC > FC-Lab6pts > FC-6KPa > FC-LabSWRC > FC-10KPa > FC-33KPa. The treatment FC-Lab6pts has the relative accuracy closest to 100% and can be a practical alternative to PC. The use of 4, 6, 8 or 10 points for modeling the SWRC does not interfere with the quality of the FC estimated by the Dexter inflection point method, which is much more efficient for experiments of this nature. The use of potentials -10 kPa and -33 kPa is not adequate to estimate FC in tests with pots in a greenhouse.